AKTIVITAS ANTIKANKER EKSTRAK AIR DAUN SINGKONG (Manihot esculenta Crantz) MENTAH DAN REBUS PADA SEL KANKER MCF-7 - , MANIK NUR HIDAYATI, Fatma Zuhrotun Nisaâ, STP., MP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
BACKGROUND: Cassava (Manihot esculenta Crantz) is a staple food in Indonesia. Cassava leaves is a good source of antioxidant such as Î²-carotene and vitamin C. Beside that cassava leaves also contain cyanogenic glucoside mainly linamarin. Some study shows that this active compound have anticancer activity, but processing can reduce this content. OBJECTIVE: The aim of this study is to know the anticancer activity of raw and boiled aqueous extract of cassava leaves on MCF-7 cell line METHOD: Cassava leaves is divided into two group (boiled and raw). 6 g of cassava leaves were boiled in 250 ml distilled water for 2 minutes with open lid. Then two group of cassava leaves were boiled at 65-750C in 60 ml of distilled water and further heated at 700C until final volume obtained (15 ml). The final concentration of aqueous extract was 400